The Concept of Learning in the Qur'an: A Study of Tafsir Quran Karim by Mahmud Yunus - Bermi, Wibawati; Asroriah, Fatimatul; Shodiq, Imam (Al-Lubab : Jurnal Penelitian Pendidikan dan Keagamaan Islam, 2024)
The concept of learning in the Qur'an holds significant relevance in shaping a holistic educational system that focuses not only on cognitive aspects but also on spiritual and moral dimensions. This study aims to analyze the concept of learning embedded in the Qur'an based on Tafsir Quran Karim by Mahmud Yunus. Utilizing a library research method, this research delves deeply into the tafsir to identify the learning principles proposed by Mahmud Yunus. The findings reveal that Mahmud Yunus emphasizes three main principles in learning: dialogical, gradual (tadarruj), and exemplary-based (uswah hasanah). These methods align with modern educational approaches, such as competency-based and interactive learning. Furthermore, this study identifies the relevance of these concepts to contemporary education, particularly in the context of character and moral development for students. The implications of this research include the necessity of integrating Qur'anic values into formal and non-formal education systems. However, its limitation lies in its focus on a single tafsir work, opening opportunities for comparative studies with other tafsir in future research. The originality of this research lies in its in-depth exploration of Tafsir Quran Karim by Mahmud Yunus within the educational context, a topic rarely discussed comprehensively. This study adds value to the development of Qur'an-based learning systems relevant to the challenges of globalization.